Determination of Sulphate in Water by Die Technique and the Detection of Ca+2 and Mg+2 in their Mixture - Najib, Fadhil M.; Abdulla, Ahmad M.; Zewar, Sardir (Sulaimani Journal for Pure and Applied Sciences, 2007)
The new thermometric sensor developed in this laboratory (Talanta-2007,71(l),141-148) has Been applied here for the determination of sulphate ion in water samples.A (20 ml) aliquot of standard or natural watersampleacidified with (1 ml)of (lMHCl)isplaced inthe thermometric cell. The cell is covered with the press-on lid, so that the sensor is completely covered by the liquid. The vertical stirrer is placed down the cell and stirred, When the thermal equilibrium is recorded, (0.5 ml) of (1.5M) barium acetate solution is injected rapidly by a syringe. The output signal is recorded and measured as a peak height during (30 sec.) Following the injection, and also read from the digital avometer, The calibration curve is drawn between (AmV) or (AT) vs. (ppm) sulphate. It was linear in tle range (10 - 110) ppm sulphate with 12 = 0.9991. The method was used for the determination of sulphate in different samples of water containing between 21 - 430 ppm with precision better than 5o4 and gave no significant difference when compared with a reference method at 95oh confidence limit (DOF = 6) using t-test of paired comparison. In this paper another successful test of the sensor was performed to evaluate its response fbr a mixture of Caz- and Mg2* ions.
Keywords: DIE technique; sulphate in water; a new thermometric sensor; detection ofCi and Mg2 ions in the presence of each other